The impact of core self-evaluations and person-job fit on work-related outcomes - Zhang, Zongguo; Yan, Zhen (Frontiers in Psychology, 2024)
Introduction The aim of this study is to explore the mediating effect of emotional exhaustion (EE) between core self-evaluations (CSE), person-job fit (PJ fit) and service recovery performance (SRP). The current research also examines whether organizational dehumanization (OD) moderates the relationship between two antecedents, EE and SRP. Methods We collected time-lagged and multi-source data from star-rated hotels in three cities in China. In particular, direct supervisors of frontline employees (FLEs) rated their SRP (N = 32 supervisors and their 212 immediate employees). The hypotheses were gauged via PROCESS (version 3.4). Results The results indicate that CSE and PJ fit alleviate FLEs’ EE, which subsequently advances their SRP. OD moderates the direct impact of two antecedents on EE and SRP. Moreover, OD moderates the indirect influence of two antecedents on SRP through EE. Discussion The hospitality literature currently lacks an in-depth understanding of the underlying mechanism through which CSE and PJ fit affect FLEs’ SRP. This study incorporates EE as a mediator of the CSE’s and PJ fit’s impact on SRP, and to the authors’ knowledge, this is the first attempt to evaluate whether OD moderates the direct influence of CSE and PJ fit on SRP and the indirect impact of CSE and PJ fit on the aforementioned outcome via EE.